Mimesophobia and rhetorics of the contagion: fear of the poem as a political instrument in Plato’s Republic - Ríos Gutiérrez, Iván de los (ΠΗΓΗ/FONS, 2020)
This paper focuses on fear of artistic contagion and its political dimension in Plato’s Republic . For Plato fear is a rhetorical and pedagogical device for a new rational configuration of individuals and community. An instrument that feeds on the political passion par excellence: fear, and, more precisely, fear of contagion, fear of disease and loss of self-control.